Quantifying desertification in the Qinghai Lake Basin - Wang, Siqing; Ma, Li; Yang, Liping; Long, Xinyuan; Guan, Chao; Zhao, Changming; Chen, Ning (Frontiers in Environmental Science, 2024)
Desertification in the context of global change and intensified anthropogenic activities poses a huge challenge to the sustainable development of the Earth’s systems, including the Qinghai Lake Basin, which is located in the Tibetan Plateau. However, we know little about desertification in the Qinghai Lake Basin, which is an urgent and important issue. To that end, this study used the enhanced vegetation index (EVI) and the albedo data from MODIS satellites to explore this issue. Results based on vegetation cover (FVC) calculated from EVI indicated that desertification in the Qinghai Lake Basin had reversed over the last 20 years, and the heavily desertified areas were concentrated along the northwestern to northern basin boundaries and on the sandy eastern shore of Qinghai Lake. More interestingly, we found that the relationship between albedo and EVI showed a “V” shape instead of the traditional monotonic trapezoid, which may be related to multiple factors such as soil moisture, soil type, and spatial scale of sampling. This study unfolds the spatial and temporal distribution of desertification in the Qinghai Lake Basin quantitatively and emphasizes the threshold of the desertification process revealed in the EVI-albedo feature space, which sheds light on the monitoring of desertification in alpine areas.